Persepsi dan Realitas: Analisis Fenomena Penyalahan Guru dalam Disiplin Peserta Didik di Sekolah Dasar - Sundari Arif, Siti; Ode Linda Sawitri, Wa; Ode Darma Alisafitri, Wa; Lilianti, Lilianti; Nasir, Nasir (Magister Administrasi Pendidikan, Universitas Muhammadiyah Kendari, 2025)
This study aims to analyze the phenomenon of blaming teachers for disciplining students in elementary schools, focusing on the gap between public perceptions and on-ground realities. Discipline is a crucial element in shaping students' character; however, teachers' disciplinary actions are often perceived as excessive, leading to accusations of ethical violations or abuse. This research employs a qualitative approach with a phenomenological method, involving in-depth interviews with teachers, students, parents, and school officials from three urban elementary schools. The findings reveal that negative public perceptions of teachers' disciplinary actions are frequently based on incomplete information, lacking an understanding of the school context and dynamics. On the other hand, some teachers acknowledge the need for more training in non-violent classroom management, influencing their disciplinary approaches. These findings highlight the importance of transparent communication between schools and parents and the need for intensive teacher training on empathy-based discipline management. This study contributes to formulating strategies to reduce misunderstandings between communities and schools and supports the creation of a more harmonious educational environment.